The Co-evolution of Friendship and Power Relations in a Men's Prison Unit - Hashimi, Sadaf (Journal of quantitative criminology, 2024)
Objectives Despite renewed research interest in prison social organization, little is known about how relationships that constitute the prison social system develop and change. The current study aims to understand the processes that link friendship and power within a prison unit over time. Method We examine longitudinal data on friendship and attributions of power collected from 274 residents in a Pennsylvania medium-security prison unit. We use a stochastic actor-oriented model to evaluate selection mechanisms that influence these relations and ascertain their temporal association. Results We find different mechanisms responsible for friendship selections and power attributions. Friendships are primarily driven by attribute-based mechanisms, while power attributions are driven by network-based properties. Nevertheless, these two facets of social structure are interdependent, with friendships operating as building blocks for the development of power hierarchy in prison. Conclusion By conceptualizing social structure as a multidimensional, fluid entity, we identify the unique roles that power and friendship relations play in recreating the prison social system. We maintain that understanding social structure in prison settings can provide insight into institutional adjustments and post-release expectations.